2012
DOI: 10.1186/1475-925x-11-14
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of the host reactions to the biodegradation of the two novel magnesium alloys ZEK100 and AX30 in an animal model

Abstract: BackgroundMost studies on biodegradable magnesium implants published recently use magnesium-calcium-alloys or magnesium-aluminum-rare earth-alloys.However, since rare earths are a mixture of elements and their toxicity is unclear, a reduced content of rare earths is favorable. The present study assesses the in vivo biocompatibility of two new magnesium alloys which have a reduced content (ZEK100) or contain no rare earths at all (AX30).Methods24 rabbits were randomized into 4 groups (AX30 or ZEK100, 3 or 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 65 publications
2
63
0
Order By: Relevance
“…In this direction, alloys of Mg with strontium (Sr), rare earth elements, calcium (Ca), aluminum, trace levels of manganese, zinc, zirconium (Zr), silicon, etc have been used to make new generations of orthopedic implants. [18][19][20][21][22][23][24][25][26] An important factor while designing these bioactive implant surfaces is the biological response of cells to the alloys, which ultimately correlates with the success of implants in the host tissue. The idealized biological efficacy of an implant would be where the implant material gets totally amalgamated with the newly formed osseous tissue and thereafter it disintegrates into the blood stream without causing damage to the vital organs or losing its functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, alloys of Mg with strontium (Sr), rare earth elements, calcium (Ca), aluminum, trace levels of manganese, zinc, zirconium (Zr), silicon, etc have been used to make new generations of orthopedic implants. [18][19][20][21][22][23][24][25][26] An important factor while designing these bioactive implant surfaces is the biological response of cells to the alloys, which ultimately correlates with the success of implants in the host tissue. The idealized biological efficacy of an implant would be where the implant material gets totally amalgamated with the newly formed osseous tissue and thereafter it disintegrates into the blood stream without causing damage to the vital organs or losing its functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Both alloys were chosen because of their promising biomechanical properties, and both had been evaluated in vivo in previous studies. [13][14][15][16][17][18][19][20][21] ZEK100 pins have shown promising initial mechanical stability. 15,20 Lensing et al reported good biocompatibility and an osteoconductive effect of ZEK100 in the middle ear of rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…However despite favorable mechanical properties, Mg alloys can only be considered suitable as biomaterials if elements released during the degradation of a magnesium implant are biocompatible. [67] The release of metal ions in the body is expected to be non-linear, non-homogeneous, and multifactorial, as shown in Figure1. It is affected by material properties such as grain size, manufacturing processes, shape, size, surface area, surface roughness, and biological environmental properties such as pH, fluid flow, ion and biological molecule concentrations, and evolved gas bubbles, among others.…”
Section: Discussionmentioning
confidence: 99%
“…[56,67,[70][71] They have shown that RE can be detected in the corrosion layers and that percentage increased with the implantation time. Krause et al, [56] found 58% M a n u s c r i p t increase of the RE content in the outer layer of the implant surfaces between the 3 rd and 6 th month after implantation.…”
Section: Discussionmentioning
confidence: 99%